Chasing joint work: administrators' efforts to structure teacher collaboration. (20th October 2019) - Lockton, Marie
ABSTRACT: Although the benefits of teacher collaboration have been touted, school administrators often struggle to foster productive collaboration at their sites. This study takes a deep dive into teachers' interactions to understand how administrators' efforts to engineer collaboration play out in teachers' relationships. Analysis of qualitative interview and observation data with a social network lens provides a nuanced understanding of teachers' formal and informal interactions at two schools. Findings make clear why leaders are unlikely to build effective collaborative cultures without noticing and building off of the relationships teachers have built within their existing contexts. Overly regulated meetings impacted both formal and informal relationships between teachers, and productive collaboration during formal meeting time could not be sustained in teachers' informal networks when other structural obstacles intervened. Few teachers were able to overcome either of these constraints to engage in meaningful collaboration, although the efforts of some provide insight for promoting collaborative cultures. This study provides insights for how leaders might notice and capitalise on existing relationships as well as on sometimes unintended structures to support teachers' join work.